Stevens-Johnson Syndrome and Its Manifestation in Oral Cavity - J. Vokurka; A. Fassmann; S. Zgažarová; P. Augustín; L. Izakovičová Hollá; J. Vaněk (Czech Dental Chamber, 2010)
Stevens-Johnson syndrome (SJS) is a disease with typical dermal and mucosal manifestations. The etiology is multifactorial. The characteristic skin manifestation is the occurrence of brick-red stains or papular dermatitis with central decrease, sc. iris form. In the efflorescence center blebs are formed. The mucosa of oral cavity displays planar erosions which originate from ripping off the blebs by mastication movements.At the periodontology ward of Stomatology Clinic Medical Faculty MU and FNBUSA in Brno the authors examined a nineteen-year patients with hemorrhagic crusts on the lips and erosions with exudation and fibrin cover, which occurred on the buccal mucosa. The tongue became swollen with edema with intensified white coating and later impressions of teeth. The patient suffered form increased salivation and pains during food intake and impossibility to maintain oral hygiene, being weakened and dehydrated. Two days later skin efflorescence occurred in the area of knees, loins and glans penis. The manifestations in oral cavity were treated at the periodontology ward and the patient was sent to hospitalization at the 1st Dermatovenerology Clinic Medical Faculty MU and FNBUSA in Brno.The case report presents the etiology, clinical course, diagnostics and therapy of the disease.